The strategy of modulation blood responses by surface modification with different functional groups on polyester film. Issue 10 (3rd June 2021) - Zhong, Rui; He, Zeng; Zhang, Xuejun; Han, Dingding; Wang, Hong; Liu, Jiaxin
Abstract: A main problem in the design of blood‐contacting biomaterials has been the deficiency of a systematic understanding of blood‐biomaterial interactions and the strategy to modulate blood responses. In this work, different functional groups including carboxyl (COOH), hydroxyl (OH) and zwitterionic sulfobetaine group (⊕ N ((CH3 )2 )(CH2 )3 SO3‐○‐, SMDB) were grafted on the poly (butylene terephthalate) (PBT) film to study how the functional groups modulate blood responses and in terms of interaction with the coagulation system, the complement system, and platelets. The results showed protein absorption and platelet adhesion was stronger on the PBT bearing COOH group than PBT films bearing OH and zwitterionic sulfobetaine groups (total protein (μg/cm 2 ): 32.92 ± 5.89 vs. 22.02 ± 1.44 vs. 19.09 ± 1.59; platelet adhesion (/mm 2 ): 1, 626.7 ± 120.1 vs. 1, 395.6 ± 363.3 vs. 1, 102.2 ± 373.7), which had a rougher and negatively charged surface, and the coagulation system was inhibited by binding fibrinogen (Fg) and coagulation factors. Meanwhile, PBT‐PSMDB showed anticoagulant property and induced platelet activation. As a result, complement formation on these two films were less than PBT bearing OH groups by inhibiting the coagulation system (C3a (ng/ml): 3, 745.4 ± 143.9 vs. 3, 290.9 ± 249.7 vs. 4, 887.9 ± 88.9; C5a (ng/ml): 22.1 ± 2.6 vs. 22.3 ± 1.8 vs. 27.9 ± 2.0). On the other hand, PBT bearing OH groups did not facilitate remarkable platelet adhesion and activation, and had no influence on platelet aggregation, hypotonic shock response, and coagulation system. The above results showed that the blood responses were highly interlinked, and could be modulated by grafting with different functional groups on the biomaterial surfaces. These findings may help identify a strategy to design materials with better hemocompatibility for blood contact, filtration, and purification applications.